(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This research is motivated by the fact that biographical texts are often taught using conventional methods such as lectures, reading textbooks, and completing worksheets. This results in low student interest and motivation because the material feels monotonous and lacks relevance to their daily lives. The aim of this research is to describe the use of digital media in biographical text teaching. This research is a descriptive qualitative study. The data in this study are the results of observations and interviews regarding the use of digital media in learning biographical texts. The data sources in this study were students and teachers involved in learning biographical texts using digital media. The data collection technique in this qualitative study used two main methods: observation and interviews. The data analysis technique used refers to the Miles and Huberman model, which includes three main components: data reduction, data presentation, and conclusion drawing/verification. The research results, based on observations, indicate that the use of digital media in teaching biographical texts has a very positive impact on the learning process. Interview results also indicate that learning becomes more engaging and less boring. The use of Wordwall, YouTube, and Canva makes students more active and enthusiastic, able to answer questions posed by the teacher, and makes the class feel more enjoyable. Therefore, it can be concluded that the use of digital media in teaching biographical texts has a positive and significant impact on the learning process and student learning outcomes.